Robust Sliding Mode Observer based Fault Estimation for Certain Class of Uncertain Nonlinear Systems. Issue 4 (26th September 2014) - Zhang, Jian; Swain, Akshya Kumar; Nguang, Sing Kiong
Abstract This paper proposes a new scheme for estimating the actuator and sensor fault for Lipschitz nonlinear systems with unstructured uncertainties using the sliding mode observer (SMO) technique. Initially, a coordinate transformation is introduced to transform the original state vector into two parts such that the actuator faults only appear in the dynamics of the second state vector. The concept of equivalent output error injection is then employed to estimate the actuator fault. The effects of system uncertainties on the estimation errors of states and faults are minimized by integrating an <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj1wg3xgrc" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />ℋ∞</alternatives> uncertainty attenuation level into the observer. The sufficient conditions for the state estimation error to be bounded and satisfy a prescribed <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj1wg3xgm5" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />ℋ∞</alternatives> performance are derived and expressed as a linear matrix inequality (LMI) optimization problem. Furthermore, the proposed actuator fault estimation method is extended to sensor fault estimation. Finally, the effectiveness of the proposed scheme in estimating actuator and sensor faults has been illustrated considering an example of a single‐link flexible joint robot system.